Detection of Escherichia coli and associated β-lactamases genes from diabetic foot ulcers by multiplex PCR and molecular modeling and docking of SHV-1, TEM-1, and OXA-1 β-lactamases with clindamycin and piperacillin-tazobactam. - Shailesh K Shahi (Public Library of Science (PLoS), 2013)
Diabetic foot ulcer (DFU) is a common and devastating complication in diabetes. Antimicrobial resistance mediated by extended-spectrum β-lactamases (ESBLs) production by bacteria is considered to be a major threat for foot amputation. The present study deals with the detection of Escherichia coli and the prevalence of bla(TEM), bla(SHV) and bla(OXA) genes directly from biopsy and swab of foot ulcers of diabetic patients. In total, 116 DFU patients were screened, of which 42 suffering with severe DFUs were selected for this study. Altogether 16 E. coli strains were successfully isolated from biopsy and/or swab samples of 15 (35.71%) patients. ESBL production was noted in 12 (75%) strains. Amplification of β-lactamase genes by multiplex PCR showed the presence of bla(CTX-M) like genes in 10 strains, bla(TEM) and bla(OXA) in 9 strains each, and bla(SHV) in 8 of the total 16 strains of E. coli. Out of the ten antibiotics tested, E. coli strains were found to be resistant to ampicillin (75%), cefoxitin (56.25%), cefazolin (50%), meropenem (37.5%), cefoperazone (25%), cefepime (31.25%), ceftazidime (56.25%), and cefotaxime (68.75%) but all showed sensitivity (100%) to clindamycin and piperacillin-tazobactam. 3D models of the most prevalent variants of β-lactamases namely TEM-1, SHV-1, OXA-1, and ESBL namely CTX-M-15 were predicted and docking was performed with clindamycin and piperacillin-tazobactam to reveal the molecular basis of drug sensitivity. Docking showed the best docking score with significant interactions, forming hydrogen bond, Van der Waals and polar level interaction with active site residues. Findings of the present study may provide useful insights for the development of new antibiotic drugs and may also prevent ESBLs-mediated resistance problem in DFU. The novel multiplex PCR assay designed in this study may be routinely used in clinical diagnostics of E. coli and associated bla(TEM), bla(SHV), and bla(OXA) like genes.